(untitled) (Impetus, 2021)
The objective of this study was to analyze the relationship between the level of social pressure and the perception of body image and sociodemographic characteristics in adolescents, with a sample of 138 participants, first and second year of diversified secondary education of three public educational institutions of the municipality Campo Elías, Merida state, Venezuela, intentionally selected. A cross-sectional descriptive field study was performed, the sample was represented by 47.1% of the male gender and 52.9% of the female gender. The average age for adolescents was 16.09 years. 24.6% were perceived to be thin, 66.7% were normal and 8.7% were overweight. Differences in pressure levels in relation to sociodemographic variables (age, gender and socioeconomic status) were not statistically significant. However, the differences found in the level of social pressure with respect to body image perception were statistically significant (F = 8,099 p = 0,000). Conclusion: Adolescents with overweight body image perception are more likely to feel greater social pressure because of physical appearance.